(3GdYed HGdUajMI GdCaGbjI PGJ GdLfhHs
(3ChdgG (B:s
(3cjajI GdYed HGdUajMI GdBaGbjI PGJ GdLfhH hajgG CHhGH GdChd (B: (3ai Yed MUI Gdejd heYQaI LgJg s
(3BNQgG (B:s
(3hhVYfG GdchcH Ydi GdCab hYdefG GdTHcI HbOQ eG MUd dfG ef GdOGFQI GdeTQb ef CLRGA adc GdHQhL agh GdWGdY dPdc GdGQJaGY hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs